Diagnostic Significance of Pleural Fluid ADA and Hematological Parameters in Pediatric Tubercular Versus Non-Tubercular Pleural Effusion (Journal of Rangpur Medical College, 2026)
Background: Pediatric pleural effusions arise from diverse etiologies, with tuberculous pleural effusion (TPE) and non-tuberculous causes being the most common. Early differentiation is essential for timely management. Objective: This study aimed to evaluate the diagnostic significance of pleural fluid ADA and hematological parameters in distinguishing pediatric tubercular versus non-tubercular pleural effusions. Methods: A cross-sectional study was conducted at Bangladesh Shishu Hospital and Institute from July 2019 to January 2022, including 47 children aged 1-18 years with pleural effusion. The diagnostic performance of pleural fluid ADA and key hematological parameters was analyzed using SPSS 26. Results: Pleural ADA was markedly higher in TPE than in non-TPE cases (90.6±52.0 vs. 36.0±11.5 U/L). TPE patients showed significantly lower total WBC counts and polymorph percentages, but higher lymphocyte percentages and ESR (P